Roe triploid temperature induction unit - WANG YIHONG; LI MINGXUE; DAI YANBIN; YOU YINGZHE; ZENG FANRONG; CHEN HEDONG (2016)
The utility model provides a roe triploid temperature induction unit, relates to aquatic products breeding equipment. A roe triploid temperature induction unit that can reach accurate accuse temperature, save the cost of labor is provided. Be equipped with the outer bucket of double -deck stainless steel, the interior bucket of individual layer stainless steel, mount, the excellent and interior bucket accuse temperature stick of outer bucket accuse temperature, the bucket is established double -deck stainless steel outside in the bucket in the individual layer stainless steel, fixed set up double -deck stainless steel outside in bucket inner wall and the individual layer stainless steel between the bucket outer wall and in being used for fixed individual layer stainless steel the bucket control warm excellently with outer barrel, outer barrel of accuse temperature stick is located between outer bucket inner wall of double -deck stainless steel and the interior bucket outer wall of individual layer stainless s